After COVID-19 lockdown: an exploratory study about the influence of mindfulness-feelings toward an individual’s outdoor lifestyle and empowerment - Borges, Ana Pinto (2023)
This study aimed to detect the relationships between mindfulness and events participation, and then between the later and psychological empowerment. Design/methodology/approach – The proposed model’s underlying hypotheses were empirically tested with data collected through an online survey addressed to a convenience sample of frequent leisure participants (n 5 199). The authors applied the structural equation model (SEM) to confirm the aforementioned relationships. To assess the adequacy of the psychometric properties of the measures, the authors performed a confirmatory factor analysis of the measurement model, with a maximum likelihood estimation method. Findings – Under the effects of the lockdown period environment, the results express a positive relationship between a mindful state of mind – related to observation/attention – and the yearnings and perceptions about the participation in events. This relationship for consistency was proven to be moderated by the perception of the participation importance to the individual subjective well-being/mental health. Due to participation insights, there was a positive effect on psychological empowerment, supporting the relationship that had been hypothesized. Originality/value – The authors propose and test a new model that contributes to the theory and examines how mindfulness behavior can effect more alluring and intense participation in events and what are the anticipated outcomes in terms of psychological empowerment.